الثقافة المعلوماتیة فى الانتاج الفکرى : دراسة ببلیومتریة - د. رباح فوزى (المجلة الدولية لعلوم المكتبات والمعلومات)
Diversity and plurality is the most important properties in the subject ofInformation Literacy literature on both the International and Arabic levels; as wellas sharing the same subject several terms.This study monitors Information Literacy trends in the Internationalliterature and the Arab world literature.The study aims of analysis this content to report all sides ofliterature in Information Literacy. As the study explain the relationship interms of similarities and differences between each of the Arabic contentand International content in this field.The study is based on a survey method for monitoring of Arabic andInternational Literature in Information literacy, and also used theBibliometric Methods to identify the trends and indicators of InformationLiteracy in Literature.